Analysis of patients with pleural effusion who underwent surgery - Muharrem, Cakmak; Evrim, Gul (Bayrakol Medical Publisher, 2020)
Aim: Pleural effusion develops due to an imbalance between the formation of pleural fluid and reabsorption cycle. In this study, we aim is to discuss the results of patients with pleural effusion treated by surgical methods. Material and Methods: Three hundred forty-five patients were analyzed. Patients were divided into 10 groups as etiological, and two groups according to the treatment procedures. The statistical significance of gender, location of the disease, underlying diseases, and the treatment of the patients were evaluated. The significance of the results was assessed by the Chi-square test or the Fisher's exact test. P < 0.05 was considered significant. Results: In empyema, right hemithorax location and exudative property were found to be significant. In congestive heart failure, male gender, left hemithorax localization and being transudative were found to be statistically significant. In malignant mesothelioma, male gender, right hemithorax location, and being exudative were statistically significant. In parapneumonic effusion, right hemithorax location and exudative property were found to be significant. In cirrhosis, female gender, right hemithorax location and being transudative were significant. In tuberculosis, being exudative was found to be significant. In paramalignant pleural effusion, exudative property was found to be significant. In pleural metastasis, male gender and being exudative were found to be statistically significant. During the treatment, tube thoracostomy was statistically significant in patients with congestive heart failure, parapneumonic effusion, pleural metastasis, cirrhosis, and undiagnosed diseases. Discussion: Pleural effusions can be managed according to the underlying diseases. Tube thoracostomy is the main method for the treatment of pleural effusions.
Keywords: Pleural Effusion; Thoracostomy; Thoracotomy; Thoracoscopy